Green infrastructure development at European Union's eastern border: Effects of road infrastructure and forest habitat loss. (15th May 2017) - Angelstam, Per; Khaulyak, Olha; Yamelynets, Taras; Mozgeris, Gintautas; Naumov, Vladimir; Chmielewski, Tadeusz J.; Elbakidze, Marine; Manton, Michael; Prots, Bohdan; Valasiuk, Sviataslau
Abstract: The functionality of forest patches and networks as green infrastructure may be affected negatively both by expanding road networks and forestry intensification. We assessed the effects of (1) the current and planned road infrastructure, and (2) forest loss and gain, on the remaining large forest landscape massifs as green infrastructure at the EU's eastern border region in post-socialistic transition. First, habitat patch and network functionality in 1996–98 was assessed using habitat suitability index modelling. Second, we made expert interviews about road development with planners in 10 administrative regions in Poland, Belarus and Ukraine. Third, forest loss and gain inside the forest massifs, and gain outside them during the period 2001–14 were measured. This EU cross-border region hosts four remaining forest massifs as regional green infrastructure hotspots. While Poland's road network is developing fast in terms of new freeways, city bypasses and upgrades of road quality, in Belarus and Ukraine the focus is on maintenance of existing roads, and no new corridors. We conclude that economic support from the EU, and thus rapid development of roads in Poland, is likely to reduce the permeability for wildlife of the urban and agricultural matrix around existing forest massifs. However, the four identified forest massifs themselves, forming the forest landscape green infrastructure at the EU's east border, were little affected by road development plans. In contrast, forest loss inside massifs was high, especially in Ukraine. Only in Poland forest loss was balanced by gain. Forest gain outside forest massifs was low. To conclude, pro-active and collaborative spatial planning across different sectors and countries is needed to secure functional forest green infrastructure as base for biodiversity conservation and human well-being. Highlights: In the EU forests generally do form a functional green infrastructure. Eastern Europe has so far retained green infrastructure better than the EU in the west. Frontiers of economic development is a potential threat to green infrastructure. Intensification of forestry is negative, but so far not road development. Green infrastructure is a concrete and suitable topic for West-East cooperation.